Mapping of Tablet PC Based On Consumer Perception (Case Study of Bandung Electronic Center Visitors) - Dini Turipanam Alamanda; Gamal Argi; Arif Partono (Forum Manajemen Indonesia (FMI), 2014)
Gadget development is becoming a phenomenon which attract the world’s attention today. Sophisticated telecommunications technology encourages the creation of newgadget especially Tablet PC. More and more people using this gadget to replace their computer use. The purpose of this study was to mapthe position of several Tablet PC brands such as Apple, Samsung, Smartfren, Acer, and ASUS based onthe perception of Bandung Electronic Center(BEC) visitors. Each day, around 25.000-40.000 visitors visit the BEC which is the largest electronic mall in Bandung. This is an exploratory reseach using the descriptive method. Multidimensional scaling technique used to mapped the 5 Tablet PC brandsinto six dimensions; product feature, brand, price, battery consumption (endurance), lifestyle and design. The questionnaires were delivered to 100 respondents using purposive sampling method. The results of this study indicated that Apple is still the best for product feature based on consumer perceptions . As for the best brand the winner is Samsung followed by Apple, ASUS, Acer and Smartfren. Based on price dimension the cheapest Tablet PC is Smartfren and Apple is the most expensive. Samsung is also the winner in the field of battery power consumption and Acer is the worst. The best Tablet PC in the field of the lifestyle is Samsung followed by Apple, ASUS, Acer and Smartfren. Finally, Tablet PC with the best design also goes to Samsung then followed by Apple, ASUS, Acer and Smartfren. Keywords: Consumer Perseption,, Positioning, Multidimensional Scaling Technique, TabletPC